Calculation of Raman optical activity spectra for vibrational analysis. Issue 9 (7th May 2015) - Mutter, Shaun T.; Zielinski, François; Popelier, Paul L. A.; Blanch, Ewan W.
<x xml:space="preserve">Abstract</x> This review provides the necessary knowledge to accurately model ROA spectra of solvated systems and interpret their vibrational characteristics.